The Epidemiology and Impact of Social Trauma: Preliminary Results from a Population Study among Icelandic Women - Arnar Guðjón Skúlason 1991- (2018)
This study sought to address and move forward the unproductive Criterion A debate on what constitutes a traumatic stressor that is likely to lead to symptoms of posttraumatic stress disorder (PTSD). We propose that there exist at least two types of trauma; threat-to-life trauma and social trauma. The impact of trauma generally, and social trauma specifically, on psychopathology was investigated in a large epidemiological sample of Icelandic women. All adult women currently residing in Iceland were invited to respond to an online questionnaire, whereby they reported detailed socio-demographic data, lifetime history of exposure to traumatic events, and current psychopathology, including measures of PTSD and social anxiety disorder (SAD). Preliminary results based on a sample of 12,564 women (M_age=43.5) showed that about 25% of participants regarded a traumatic social event as their worst traumatic experience and many of these were associated with high scores of PTSD symptoms and high rates of probable PTSD and SAD diagnoses. Primarily social traumas, in which participants experienced high rejection/humiliation but low threat to life, had an impact on psychopathology measures and functional variables comparable to primarily threat to life traumas, in which participants experienced high threat to life but low rejection/humiliation. Furthermore, traumas involving a combination of high threat to life and rejection/humiliation had the strongest association with PTSD symptoms, SAD symptoms, generalized anxiety, depression, and suicidality. Among participants with a probable SAD diagnosis, more than 64% had probable PTSD in response to a traumatic event involving severe rejection/ humiliation (i.e. social PTSD). These findings may have important implications for the conceptualization of trauma and theoretical models of both PTSD and SAD. They could also have substantial clinical implications, especially for the treatment of individuals who develop PTSD and SAD in response to social trauma.